MENAKAR TINGKAT KEPUASAN MAHASISWA SPS. UHAMKA TERHADAP KUALITAS PENYELENGGARAAN PENDIDIKAN - Safi'i, Imam; Nuriadin, Ishaq (Manajemen Pendidikan, 2020)
The level of student satisfaction with the process of organizing education has a very important role in supporting the existence of an institution. This study aims to describe the level of satisfaction of SPs students. UHAMKA for the implementation of education that takes place at the Graduate School. UHAMKA. The satisfaction aspects measured include satisfaction with the leadership of the leadership of the institution and study program, teaching from lecturers, academic services from the teaching staff, procurement of learning facilities and infrastructure, as well as the impact of studies at UHAMKA on personal or career development prospects. The approach used in this research is a quantitative approach with survey methods. The media survey using the Google form provided to a number of respondents, namely 191 graduates for the 2018/2019 academic year. The results showed that the level of satisfaction of SPs students. UHAMKA is very high (very satisfying), which is 88.03. The results of this study can be used as a foundation for evaluations and efforts for continuous improvement for managers.